Adaptive Strategy and Sustainability in the National Fertilizer Industry under VUCA Conditions: A Systematic Literature Review and Bibliometric Analysis - Niera Feblidiyanti; Ahmad Syafrudidin Indrapriyatna; Elita Amrina; Franka Hendra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
The national fertilizer industry faces volatile energy and raw-material prices, global supply disruptions, policy uncertainty, subsidy pressures, and rising decarbonization expectations. This study reviews recent literature on adaptive strategy and sustainability in the fertilizer industry under volatile, uncertain, complex, and ambiguous (VUCA) conditions. A systematic literature review following PRISMA 2020 was combined with bibliometric analysis using bibliometrix/Biblioshiny. The final search was conducted on 10 December 2025 in Scopus and ScienceDirect for publications from 2020 to 2025. A total of 824 records were identified, 63 duplicates were removed, 761 titles and abstracts were screened, 173 records were retained for bibliometric mapping, and 23 full-text articles were selected for in-depth synthesis. An extended literature review matrix of 164 cleaned articles was used to triangulate themes, methods, and research gaps. The results show that sustainability, low-carbon fertilizer transformation, supply chain resilience, digital transformation, adaptive strategy, and VUCA-driven uncertainty dominate the literature, but their integration into a strategy-oriented framework remains limited. The novelty of this study lies in developing an integrative framework linking VUCA pressures, dynamic capabilities, supply chain resilience, adaptive strategic responses, and sustainability performance for national fertilizer industry transformation